2010
DOI: 10.1108/02621711011039169
|View full text |Cite
|
Sign up to set email alerts
|

Age cohort effects, gender, and Romanian leadership preferences

Abstract: Purpose -This study aims to examine preferences for both transformational and transactional leadership behavior for gender-and age-based cohort differences. The purpose of this research is to enhance leadership and organizational change initiatives in Romania via the identification of age cohort and gender effects with respect to attitudes towards common leadership behaviors. Design/methodology/approach -The research is conducted via a survey through the administration of questionnaires. The sample consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
2
14
2
Order By: Relevance
“…This means the age of hotel managers had some influence on their leadership style and competencies. These findings are similar to the study of Fein, Tziner, and Vasiliu (2010), who found that older managers (35 years and above) implement more transformational leadership behaviors, while younger managers preferred autocratic leadership behaviors. Blayney and Blotnicky (2010) Downloaded by [University of West Florida] at 05:15 05 January 2015 examined the relationships between the demographic factors of age, gender, education, and tenure of leadership competencies in Canadian hotel GMs.…”
Section: Relationships Between Leadership Competency and Hotel Gms' Csupporting
confidence: 92%
“…This means the age of hotel managers had some influence on their leadership style and competencies. These findings are similar to the study of Fein, Tziner, and Vasiliu (2010), who found that older managers (35 years and above) implement more transformational leadership behaviors, while younger managers preferred autocratic leadership behaviors. Blayney and Blotnicky (2010) Downloaded by [University of West Florida] at 05:15 05 January 2015 examined the relationships between the demographic factors of age, gender, education, and tenure of leadership competencies in Canadian hotel GMs.…”
Section: Relationships Between Leadership Competency and Hotel Gms' Csupporting
confidence: 92%
“…Other investigations also survey CEOs or managers (e.g., Egri and Herman, 2000;Fein et al, 2010;García Morales et al, 2008a;Sarros et al, 2008). Although existing evidence suggests that self-reports of leadership are valid measures (e.g., Yukl and Van Fleet, 1991), interviewing and administering questionnaires to all other organizational members (and not only to subordinates) would have been preferable to verify leaders' selfreport of their behavior (e.g., Egri and Herman, 2000;Sarros et al, 2008).…”
Section: Conclusion and Future Researchmentioning
confidence: 97%
“…These items are duly adapted to the present study. As in other similar studies, the CEOs indicated their perceptions about the behavior of transformational leadership in the organization (e.g., Fein et al, 2010;Sarros et al, 2008). The authors used a confirmatory factor analysis to validate a Likert-type 7-point scale (1 "totally disagree," 7 "totally agree"), which required deletion of Item .…”
Section: Transformational Leadershipmentioning
confidence: 98%
“…Although there are a few studies comparing followers' preference for either transformational or transactional leadership (Brain and Lewis 2004;Fein et al 2010;Singer and Singer 2001), or between charismatic leadership, or relationship-oriented and task-oriented leadership (Ehrhart and Klein 2001), to our knowledge, there is no study comparing followers' preference for paternalistic and transformational leadership. However, the growing number of western organizations which seek to expand their business horizons globally, and the prevalence of paternalistic leadership in many regions such as Asia Pacific, the Middle East, and Latin America (Aycan 2006;Pelligrini and Scandura 2008) make this a legitimate inquiry.…”
Section: Paternalistic and Transformational Leadershipmentioning
confidence: 99%